Illness Perceptions and Fatigue in Systemic Vasculitis. Issue 11 (28th October 2013) - Grayson, Peter C.; Amudala, Naomi A.; Mcalear, Carol A.; Leduc, Renée L.; Shereff, Denise; Richesson, Rachel; Fraenkel, Liana; Merkel, Peter A.
<x xml:space="preserve">Abstract</x> Objective To compare illness perceptions among patients with different forms of vasculitis, identify risk factors for negative illness perceptions, and determine the association between illness perceptions and fatigue. Methods Participants were recruited from an online vasculitis registry to complete the revised Illness Perception Questionnaire (IPQ‐R). The mean scores on each IPQ‐R dimension were compared across different types of vasculitis. Cluster analysis and stepwise regression identified predictors of negative illness perception. Fatigue was measured using the general subscale of the Multidimensional Fatigue Inventory (MFI‐20). Patient‐reported measures of disease activity and IPQ‐R dimensions were assessed in relation to MFI‐20 scores using linear regression in sequential, additive models with model‐fit comparisons. Results In total, 692 participants with 9 types of vasculitis completed the IPQ‐R. For 6 of the 8 IPQ‐R dimensions, there were no significant differences in mean scores between the different vasculitides. Scores in the identity and cyclical dimensions were significantly higher in Behçet's disease compared with other types of vasculitis (13.5 versus 10.7 for identity and 4.0 versus 3.2 for cyclical [P < 0.05]). Younger age (odds ratio [OR] 1.04, 95% confidence interval [95% CI] 1.02–1.06), depression (OR 4.94, 95% CI 2.90–8.41), active disease status (OR 2.05, 95% CI 1.27–3.29), and poor overall health (OR 3.92, 95% CI 0.88–17.56) were associated with negative illness perceptions. The sequential models demonstrated that the IPQ‐R dimensions explained an equivalent proportion of variability in fatigue scores compared with measures of disease activity. Conclusion Illness perceptions are similar across different types of vasculitis, and younger age is a risk factor for negative illness perceptions. Illness perceptions explain differences in fatigue scores beyond what can be explained by measures of disease activity.